Constructing arabinofuranosidases for dual arabinoxylan debranching activity. Issue 1 (6th October 2017) - Wang, Weijun; Andric, Nikola; Sarch, Cody; Silva, Bruno T.; Tenkanen, Maija; Master, Emma R.
Abstract: Enzymatic conversion of arabinoxylan requires α‐L‐arabinofuranosidases able to remove α‐L‐arabinofuranosyl residues (α‐L‐Ara f ) from both mono‐ and double‐substituted D‐xylopyranosyl residues (Xyl p ) in xylan (i.e., AXH‐m and AXH‐d activity). Herein, SthAbf62A (a family GH62 α‐L‐arabinofuranosidase with AXH‐m activity) and BadAbf43A (a family GH43 α‐L‐arabinofuranosidase with AXH‐d3 activity), were fused to create SthAbf62A_BadAbf43A and BadAbf43A_SthAbf62A. Both fusion enzymes displayed dual AXH‐m, d and synergistic activity toward native, highly branched wheat arabinoxylan (WAX). When using a customized arabinoxylan substrate comprising mainly α‐(1 → 3)‐L‐Ara f and α‐(1 → 2)‐L‐Ara f substituents attached to disubstituted Xyl p (d‐2, 3‐WAX), the specific activity of the fusion enzymes was twice that of enzymes added as separate proteins. Moreover, the SthAbf62A_BadAbf43A fusion removed 83% of all α‐L‐Ara f from WAX after a 20 hr treatment. 1 H NMR analyses further revealed differences in SthAbf62A_BadAbf43 rate of removal of specific α‐L‐Araf substituents from WAX, where 9.4 times higher activity was observed toward d‐α‐(1 → 3)‐L‐Ara f compared to m‐α‐(1 → 3)‐L‐Ara f positions. Abstract : Bioprocessing of arabinoxylan requires α‐L‐arabinofuranosidases with dual arabinoxylan debranching activity (i.e. AXH‐m, d activity). Herein, SthAbf62A (a family GH62 α‐L‐arabinofuranosidase with AXH‐m activity) and BadAbf43A (a family GH43 α‐L‐arabinofuranosidase with AXH‐d3 activity), were fused to create SthAbf62A_BadAbf43A and BadAbf43A_SthAbf62A. Both fusion enzymes displayed dual AXH‐m, d and synergistic activity towards native wheat arabinoxylan (WAX). Moreover, the SthAbf62A_BadAbf43A removed 83% of all α‐L‐Ara f from WAX after treatment.